Dynamics of value chain in Climate Resilient Vegetable Practices - Acharya, Ujjal Raj (Economic Journal of Nepal, 2018)
The vegetable production is based on the farmer's initiation into which the processes combine with the climate resilient techniques and marketing strategy. The study is also an introduction of an integrated process of climate resilient practices that can help in coping with climate change related problems. The main objective of the study is to analyze the value chain of climate resilient vegetable farming practices. The study was carried out in Udayapur district of Nepal. The data used for the study were from Himalica pilot project initiated by ICIMOD. Primary data were collected from 300 vegetable farmer's households using a semi-structured questionnaire and checklist for interviews with farmers groups. The value chain study shows that profit of farmers depends on the market type and farmer's revenue increases when they sell their produce through farmer's co-operatives. The farmers need material support, technology as well as farmers group organization in order to increase the profit and to mitigate the risk from climate change and climate variability. The study found that value chain of vegetable farming has benefits in terms of social, economic and environmental aspects.